Tinjauan Hukum Islam terhadap Pengadaan Walimatul ‘Ursy pada Masa Pandemi Covid-19 - Afrohah Afrohah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2021)
In Indonesia, the Covid-19 pandemic is considered a national disaster so that large-scale social restrictions are imposed by limiting certain activities. One of them is the implementation of Walimatul 'Ursy which is a recommendation for Islam and Culture that has been ingrained in Indonesia. Many Local Government Officials prohibit the procurement of Walimatul 'Ursy during the Covid-19 Pandemic because it is considered a violation. One of them is in Wonogiri Regency, the Wonogiri Regency Covid-19 Task Force often disperses residents who are desperate to hold Walimatul 'Ursy so many people are in a dilemma between having to hold Walimatul 'Ursy or not. The purpose of this study is to analyze the Islamic Law review to Procurement of Walimatul ‘Ursy During the Covid-19 Pandemic” (Case Study in Jatipurno District, Wonogiri Regency), as the contribution of researchers to be used as community references. This type of research uses a qualitative approach. The research was conducted for months from March 2021 until June 2021. The results of this study concluded that the Procurement of Walimatul 'Ursy during the Covid-19 Pandemic Period in Jatipurno Wonogiri District was following the Government Regulation (Ulil Amri) which was based on the benefit of the people. The procurement is considered to be quite orderly, so the legal status of the implementation of Walimatul 'Ursy during the Covid-19 Pandemic Period in Jatipurno Wonogiri District is allowed, provided that it obtains official permission from the local government and is able to comply with the technical terms and conditions for its implementation.